Identifikasi Daerah Potensi Longsor Melalui Pengamatan Erosi Berdasarkan Analisis Nilai Suseptibilitas Magnetik Tanah (Studi Kasus: Daerah Tonggo Kanagarian Tigo Koto Silungkang, Kecamatan Palembayan, Kabupaten Agam, Sumatera Barat) - Haris Luthfi; Arif Budiman (Universitas Andalas, 2024)
based on soil magnetic susceptibility (MS) analysis in Tonggo Kenagarian Tigo Koto Silungkang area, Palembayan District, Agam Regency, West Sumatra Province. Soil samples were taken from on two slopes, namely Track A and Track B and one reference point. Samples were measured for low frequency MS (χlf) and frequency-dependent MS (χfd). The results showed that χlf and χfd respectively ranged from 183.7 to 435.5 ×10-8 m3kg-1 and 1.2 to 4.6% (Track A), 416.9 to 600.4 ×10-8 m3kg-1 and 0.9 to 2.2% (Track B), and 365.8 to 638.3 ×10-8 m3kg-1 (reference point). The χlf value of sample of each point on Track A is much smaller than the χlf value of sample of the reference point, while the χlf value of sample of each point on Track B is almost close to the χlf value of sample of the reference point. These results indicate that the slopes of Track A experienced more severe erosion than Track B. The distribution of χlf and χfd values for Track A was relatively straight, whereas for Track B the increase in the χlf value was not followed by an increase in the χfd value. These results indicate that Track A experienced anthropogenic disturbance. The slope of Track A has a greater landslide potential than the slope of Track B.